A Study on Modeling of Effective Series Resistance for Lithium-ion Batteries under Life Cycle Consideration. (August 2019) - Somakettarin, N; Pichetjamroen, A
Abstract: This paper presents a modeling of effective series resistance for Lithium-ion batteries, which is focusing on the effect of life cycles in aging cells during operations. A computer-based sequential control system is developed to prepare aging cells and automatically characterize the information of testing batteries. Several aspects of testing parameters during the charge and discharge, such as characteristics of the effective series resistance, amplitudes of the pulse current, changes of the increasing resistance, state of charge, capacity and operating cycles, are considered and analyzed to implement in the effective series resistance model. A methodology based on the experiment of pulse tests is applied as sequential steps for modeling the effective series resistance with life cycle consideration. Comparison results between the proposed model and measured values over the life cycle of the battery show the satisfactory verification with the maximum error lower than 4%.